Content Analysis of Online Commenters on Sexism in the 2008 Presidental Campaign. - Gruber, Kathryn (My University, 2009)
Hillary Clinton and Sarah Palin played prominent roles in the 2008 presidential primary and general campaigns, inviting a discussion of sexism. The unstoppable growth of the Internet has allowed news consumers to share opinions with ease. In this study, I compared comments left on the comment board following an article on perceived sexism by Clinton supporters to the comments left on the comment board following an article on perceived sexism by Palin supporters. The comments were coded for sexist content using positive/negative versions of subtle, covert, and blatant sexism. The results indicate that 75.9% of the comments about Palin were negatively sexist, while only 67.2% of the comments about Clinton were negatively sexist. Results suggest that factors influencing sexist perceptions may include the candidate?s family, the candidate?s stage in his or her political career, and pre-existing commenter characteristics.
Keywords: Internet; Forums (Discussion and debate); Sarah Palin; Hillary Clinton; Sexism; Women in government; Elections, United States; Presidential candidates; Presidential campaigns